Chinese expert consensus on the diagnosis and treatment of thymic epithelial tumors. Issue 12 (16th March 2023) - Xu, Chunwei; Zhang, Yongchang; Wang, Wenxian; Wang, Qian; Li, Ziming; Song, Zhengbo; Wang, Jiandong; Yu, Jinpu; Liu, Jingjing; Zhang, Shirong; Cai, Xiuyu; Wu, Ming; et al.
Abstract: Thymic epithelial tumors (TETs) are a relatively rare type of thoracic tumor, accounting for less than 1% of all tumors. The incidence of TETs is about 3.93/10000 in China, slightly higher than that of European and American countries. For resectable TETs, complete surgical resection is recommended. Radiotherapy or chemotherapy may be used as postoperative adjuvant treatment. Treatment for advanced, unresectable TETs consist mainly of radiotherapy and chemotherapy, but there is a lack of standard first‐ and second‐line treatment regimens. Recently, targeted therapies and immune checkpoint inhibitors have shown promising outcomes in TETs. Based on the currently available clinical evidences and the opinions of the national experts, the Thymic Oncology Group of Yangtze River Delta Lung Cancer Cooperation Group (East China LUng caNcer Group, ECLUNG; Youth Committee) established this Chinese expert consensus on the clinical diagnosis and treatment of TETs, covering the epidemiology, diagnosis, treatment, prognosis and follow‐up of TETs.